Multicentric adrenocorticotropic hormone -producing steroid cell tumor of the fallopian tube & broad ligament in a 15 year old girl. (1st September 2020) - Hamdy, Omar; Saleh, Gehad A.; Eldegwi, Sara A.; Elsayed, Mohammed; Metwally, Islam H.; Naguib, Reham; Setit, Ahmed
Abstract: Steroid cell tumors occur usually in the ovaries with very few reported cases of extra-ovarian origin. Our patient was a fifteen year old female, complaining from secondary amenorrhea and voice deepening. Values of serum cortisol, DHEA, FSH & LH were normal. Serum Testosterone was elevated while ACTH-pm was markedly elevated. MRI described bilateral solid para-ovarian masses. Exploration revealed two bilateral tubal extraluminal cysts & a right broad ligament cyst which were all excised. Pathological examination led to the diagnosis of steroid cell tumor. Serum testosterone & ACTH returned to normal levels after surgery with subsequent regression of the virilizing symptoms. We can conclude that extra-ovarian steroid cell tumors are extremely rare. They are usually presented with virilizing symptoms and hormonal abnormalities. Surgery is the main line of treatment.